A cross-cultural perspective on feeling good in the context of foods and beverages. (January 2019) - Sulmont-Rossé, Claire; Drabek, Rafal; Almli, Valérie L.; van Zyl, Hannelize; Silva, Ana Patricia; Kern, Martin; McEwan, Jean A.; Ares, Gastón
Abstract: The aim of the present research was to explore consumers' conceptualization of feeling good in relation to food and beverages from a cross-cultural perspective. Participants from 14 countries across 5 continents and covering 10 languages ( N  = 8325) responded to an online survey including word association and free listing tasks related to feeling good in the context of food and beverages. Results were analyzed using inductive coding: a list of main codes was generated in English for each of the tasks, after which native speakers for each language coded the responses. Codes were grouped into categories reflecting common themes from which eight dimensions were identified. Results showed that in the context of foods and beverages, feeling good was mainly associated with specific foods and sensory and hedonic properties. Across the 14 countries, 'Sweet and fat food', 'Fruit and vegetables', and 'Protein food' were the three food categories most associated with feeling good. Emotional aspects of food consumption ('Taste good' and emotions) were also relevant. Health and nutrition-related aspects were more relevant for consumers when they were asked to think about how foods and beverages would make them feel good in the future. In other words, food-related feeling good seems to be mainly driven by sensory pleasure at present, but it is also related to nutrition and health in the future. Differences in the strength of the associations between feeling good and the identified categories were found between countries, in line with the existence of cultural differences in food habits, as well as in the importance people attach to the characteristics of foods and beverages. Results from the present work provide insights on the impact of eating and drinking on feeling good in terms of emotional, physical and social aspects, and increase knowledge about the way food and drink can contribute to general well-being. Highlights: In a food-related context, feeling good is a multi-dimensional construct. Feeling good is strongly associated with hedonic aspects of food consumption. Health and nutrition gain in salience when thinking of feeling good in the future. There are cultural differences in the conceptualization of feeling good.